Comprehensive Physiology 2012
DOI: 10.1002/cphy.c110060
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Gas Exchange

Abstract: Gas exchange is a critical process required for sufficient tissue perfusion. The environment, genetics, or a combination of the two can affect this process. Various strategies have evolved to overcome the specific gas exchange challenges in different environments and it is clear that some genes are pivotal to the development of gas exchanging organs (e.g. Bmp4). Lower partial pressure of oxygen (hypoxia), reducing the partial pressure gradient, makes gas exchange more challenging and therefore the height to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 262 publications
1
14
0
Order By: Relevance
“…A previous study performed among Turkish children aged 10 years showed that children living at high altitude (1,725 m) had higher systolic and diastolic BP levels compared with children from similar ethnic backgrounds who lived at sea level (Arslan et al 2003). Similar findings have been reported in children from Pakistan, with a prevalence of hypertension of 12.2% (Jafar et al 2005).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A previous study performed among Turkish children aged 10 years showed that children living at high altitude (1,725 m) had higher systolic and diastolic BP levels compared with children from similar ethnic backgrounds who lived at sea level (Arslan et al 2003). Similar findings have been reported in children from Pakistan, with a prevalence of hypertension of 12.2% (Jafar et al 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the decrease of partial pressure gradients hinders the exchange of gas, causing chronic insufficiency of oxygenated blood circulation (Zheng et al 2012). This results in the decrease in the blood being supplied to the kidneys and the consequent release of renin (Howden et al 2012). This process increases the vasoconstriction of arteries (Howden et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes a drop in blood supply to the kidneys, and the subsequent release of renin that contributes to the vasoconstriction of the arteries. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we included a paragraph in the discussion section describing studies from other authors that postulate that the decrease of partial pressure gradients hinders the exchange of gas, causing chronic insufficiency of oxygenated blood circulation (Zheng et al 2012). This causes a drop-in blood supply to the kidneys and the subsequent release of renin, which contributes to the vasoconstriction of arteries (Howden and Kleeberger 2012), suggesting that decreased saturation could contribute to hypertension. However, we believe that our study has added something valuable to the literature.…”
mentioning
confidence: 99%